Hyperons and massive neutron stars: vector repulsion and SU(3) symmetry - Weißenborn-Bresch, Simon Alexander; Chatterjee, Debarati; Schaffner-Bielich, Jürgen (Physical review. C, Nuclear physics, 2012)
With the discovery of massive neutron stars such as PSR J1614-2230, the question has arisen of whether exotic matter such as hyperons can exist in the neutron star core. We examine the conditions under which hyperons can exist in massive neutron stars. We consistently investigate the vector baryon-meson coupling, going from the SU(6) quark model to a broader SU(3) symmetry. We propose that the maximum neutron star mass decreases linearly with the strangeness content fs of the neutron star core as Mmax(fs)=Mmax(0)−0.6M⊙(fs/0.1), which seems to be independent of the underlying nuclear equation of state and the vector baryon-meson coupling scheme. Thus, pulsar mass measurements can be used to constrain the hyperon fraction in neutron stars.
Gesehen am 09.05.2019